2019
DOI: 10.1002/ppsc.201900235
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Colloidal and Chemical Stability in Aqueous Media of NaYF4‐Type Upconversion Nanoparticles Modified by Ligand‐Exchange

Abstract: Surface capping is an essential component of nanoparticles as it provides access to their outstanding properties in the real world. Upconversion nanoparticles are predominantly interesting for use in biological environments, due to their excellent optical properties such as the conversion of near‐infrared excitation light into emissions in the visible or UV range of the spectrum, high photostability, and the absence of any intermittence. One of the most efficient upconversion nanoparticles, consisting of lanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 53 publications
2
82
0
5
Order By: Relevance
“…NaYF 4 :20%Yb 3+ ,2%Er 3+ UCNP were synthesized according to a previously reported procedure 26 28 with some modifications 25 , 44 . Surface modifications and silica coating experiments followed published procedures 45 49 .…”
Section: Methodsmentioning
confidence: 99%
“…NaYF 4 :20%Yb 3+ ,2%Er 3+ UCNP were synthesized according to a previously reported procedure 26 28 with some modifications 25 , 44 . Surface modifications and silica coating experiments followed published procedures 45 49 .…”
Section: Methodsmentioning
confidence: 99%
“…We investigated the role of MSN physicochemical stability by measuring the fluorescence intensity change in a slightly acid medium (pH~6.5–6.7), which mimicked the tumor microenvironment’s pH. The change in fluorescence stability was related to the MSN’s chemical and/or physical changes, such as the homogeneity, degradation and aggregation of NP in the solution [ 34 ]. The degree of NP dispersity change under a slightly acid medium is shown as the polydispersity index (PDI) values presented in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates a highly positive charged surface, useful as a polycationic component for multilayer formation, as it was shown previously by our group using cationic polymeric particles with a ζ potential of ≈30 mV [ 38 ]. A further advantage is that the positive charge also provides colloidal stability in suspension [ 39 ]. X-ray diffraction studies demonstrated that OO4/DOPE 1/3 forms non-correlated bilayers even at high lipid concentrations due to electrostatic repulsion [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…A further advantage is that the positive charge also provides colloidal stability in suspension [ 39 ]. X-ray diffraction studies demonstrated that OO4/DOPE 1/3 forms non-correlated bilayers even at high lipid concentrations due to electrostatic repulsion [ 39 ]. This behavior causes the tendency to form spontaneously unilamellar vesicles.…”
Section: Resultsmentioning
confidence: 99%